THE STATE AND SOCIETY: POLITICAL UNITY DURING MARTIAL LAW - Loboda, Dmytro (Public Management and Policy, 2025)
The study is devoted to the problems of interaction between society and the government in Ukraine during the full-scale military invasion by the Russian Federation. The aim is to provide a scientific justification of the interaction as a multidimensional phenomenon (identity, institutional trust, readiness for restrictions), to identify the key risks that lead to its erosion, and to propose practical recommendations for preserving and/or strengthening unity between the government and society in Ukraine. The research combines the analysis of external serial sociological surveys conducted by both governmental and independent institutions, qualitative analysis of expert sources, and open data in order to determine the causes and mechanisms of decreasing unity between the government and society in Ukraine. The results reveal two significant trends: a high baseline level of trust in defense institutions and volunteer networks, and, at the same time, a decline in long-term optimism and growing psycho-emotional stress. Key threats to meaningful interaction have been identified, including military and psychological fatigue, socio-economic difficulties, corruption, and information attacks. The risks are systematized along with their preconditions and possible consequences for consolidation. Based on the analysis, medium-term (1–2 years) public policy measures are proposed: coordination of unity-risk monitoring, platforms for feedback and targeted coordination of assistance; modernization of the system of social payments and incentives with transparent auditing mechanisms; strengthening of independent anti-corruption procedures and open public monitoring; investment in media literacy and support for independent media. The practical significance lies in assessing the current state of unity between the government and society in Ukraine, identifying empirically confirmed risks, and formulating recommendations aimed at preserving mobilization capacity and public trust in state institutions during a protracted conflict and in the post-war period.